Importance of Social Media in Agricultural Outreach Activities - Verma, Mayur; Sharma, Yogesh (Journal of Agricultural Extension Management, 2021)
The use of social media in information exchange has enormous potential. However, there is considerable skepticism about its use for farm extension education activities; therefore, documentation of its current use for communicating farming-related information is vital. This study outlines social media’s current and prospective users in the agricultural and extension sectors.